A review of thermal absorbers and their integration methods for the combined solar photovoltaic/thermal (PV/T) modules - Wu, Jinshun; Zhang, Xingxing; Shen, Jingchun; Wu, Yupeng; Connelly, Karen; Yang, Tong; Tang, Llewellyn; Xiao, Manxuan; Wei, Yixuan; Jiang, Ke; Chen, Chao; Xu, Peng; et al. (Elsevier, 2016)
Thermal absorbers and their integration methods are critical to solar photovoltaic/thermal (PV/T) modules. These two elements directly influence the cooling effort of PV layers and as a result, the related electrical/thermal/overall efficiency. This paper conducts a critical review on the essential thermal absorbers and their integration methods for the currently-available PV modules for the purpose of producing the combined PV/T modules. A brief overview of different PV/T technologies is initially summarized, including aspects of their structure, efficiencies, thermal governing expressions and their applications. Seven different types of thermal absorbers and four corresponding integration methods are subsequently discussed and summarized in terms of their advantages/disadvantages and the associated application for various PV/T modules. Compared to traditional thermal absorbers, such as sheet-and-tube structure, rectangular tunnel with or without fins/grooves and flat-plate tube, these four types, i.e. micro-channel heat pipe array/heat mat, extruded heat exchanger, roll-bond heat exchanger and cotton wick structure, are promising due to the significant enhancement in terms of efficiency, structure, weight, and cost etc. The appropriate or suitable integration method varies in different cases, i.e. the ethylene-vinyl acetate (EVA) based lamination method seems the best option for integration of PV layer with thermal absorber when compared with other conventional methods, such as direct contact, thermal adhesive and mechanical fixing. Finally, suggestions for further research topics are proposed from five aspects. The overall research results would provide useful information for the assistance of further development of solar PV/T modules with high feasibility for widespread application in energy supply even at district or city-level in the near future.